Kontradiksi Penggunaan Hak Veto Atas Kesetaraan Prinsip Kedaulatan Anggota PBB (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2025)
The United Nations is an international organization that has very important role in maintaining world peace and security. The United Nations Charter does not provide much explicit regulation regarding Veto rights. the use of the Veto rights is community, and in this research we will discuse the regulations regarding the Veto right and its various relevance in relation to the principle of sovereignty adopted by the United Nations. That basically the regulation of the principles and principle of equality of state sovereignty has been expressly regulated in article 2 paragraph (1) of the UN Charter. The provisions are the basis for carrying out the functions of the UN as an international organization, including the basis for carrying out the functions of its main organ. Therefore, this principle becomes a guide for decision makers in the UN security council until there is no longer any reason to justify the use of the Veto right.